Biomechanical Comparison of the Temporalis Muscle Fascia, the Fascia Lata, and the Dura Mater - Pukšec, Mirjana; Semenski, Damir; Ježek, Damir; Brnčić, Mladen; Karlović, Sven; Jakovčević, Antonia; Bosanac, Goran; Jurlina, Martin (Journal of Neurological Surgery Part B: Skull Base, 2019)
The purpose of our research is to prove that elastic biomechanical characteristics of the temporalis muscle fascia are comparable to those of the fascia lata, which makes the temporalis muscle fascia adequate material for dural reconstruction in the region of the anterior cranial fossa. Fifteen fresh human cadavers, with age range from 33 to 83 years (median age: 64 years; mean age: 64.28 years), were included in the biomechanical study. Biomechanical stretching test with the comparison of elasticity among the tissues of the temporalis muscle fascia, the fascia lata, and the dura was performed. The samples were stretched up to the value of 6% of the total sample length and subsequently were further stretched to the maximum value of force. The value of extension at its elastic limit for the each sample was extrapolated from the force–extension curve and was 6.3% of the total sample length for the fascia lata (stress value of 14.61 MPa), 7.4% for the dura (stress value of 6.91 MPa), and 8% for the temporalis muscle fascia (stress value of 2.09 MPa). The dura and temporalis muscle fascia shared the same biomechanical behavior pattern up to the value of their elastic limit, just opposite to that of the fascia lata, which proved to be the stiffest among the three investigated tissues. There was a statistically significant difference in the extension of the samples at the value of the elastic limit for the fascia lata in comparison to the temporalis muscle fascia and the dura (p = 0.002; Kruskal–Wallis test). Beyond the value of elastic limit, the temporalis muscle fascia proved to be by far the most elastic tissue in comparison to the fascia lata and the dura. The value of extension at its maximum value of force for the each sample was extrapolated from the force–extension curve and was 9.9% of the sample's total length for the dura (stress value of 10.02 MPa), 11.2% for the fascia lata (stress value of 23.03 MPa), and 18.5% (stress value of 3.88 MPa) for the temporalis muscle fascia. There was a statistically significant difference in stress values at the maximum value of force between the dura and the temporalis muscle fascia (p = 0.001; Mann–Whitney U test) and between the dura and the fascia lata (p < 0.001; Mann–Whitney U test). Because of its elasticity and similarity in its mechanical behavior to the dura, the temporalis muscle fascia can be considered the most suitable tissue for dural reconstruction.
Keywords: free temporalis muscle fascia graft; dura mater; free fascia lata graft; tensile test; elasticity